Some $p$-Adic Hardy Operators and Their Commutators (Journal of Mathematical Study, 2025)
In this paper, we will study the sharp estimates of $p$-adic weighted Hardyoperator on central and noncentral weighted $p$-adic Morrey spaces. Moreover, wecan obtain the sharp bound of generalized $p$-adic Hardy operator. In addition, thecommutator that is generated by the generalized $p$-adic Hardy operator and the centralBMO function is also bounded on $p$-adic Morrey spaces.